Atomic‐Scale Investigation of the Lattice‐Asymmetry‐Driven Anisotropic Sublimation in GaN. Issue 22 (2nd June 2022) - Sheng, Shanshan; Wang, Tao; Liu, Shangfeng; Liu, Fang; Sheng, Bowen; Yuan, Ye; Li, Duo; Chen, Zhaoying; Tao, Renchun; Chen, Ling; Zhang, Baoqing; Yang, Jiajia; et al.
Abstract: Thermal sublimation, a specific method to fabricate semiconductor nanowires, is an effective way to understand growth behavior as well. Utilizing a high‐resolution transmission electron microscope (TEM) with in situ heating capability, the lattice‐asymmetry‐driven anisotropic sublimation behavior is demonstrated of wurtzite GaN: sublimation preferentially occurs along the [ 000 1 ¯ 0001 ] and [0001] directions in both GaN thin films and nanowires. Hexagonal pyramidal nanostructures consisting of six semipolar 1 1 ¯ 01 { 1101 } planes and one (000 1 ¯ 1 ) plane with the apex pointing to the [0001] direction are generated as a sublimation‐induced equilibrium crystal structure, which is consistent with the lattice‐asymmetry‐driven growth behaviors in wurtzite GaN. These findings offer a new insight into the thermal stability of wurtzite GaN and provide essential background for tailoring the structure of III‐nitrides for atomic‐scale manufacturing. Abstract : Anisotropic sublimation behavior of wurtzite GaN is directly demonstrated using in situ heating transmission electron microscopy (TEM) technique. Sublimation preferentially occurs along [0001] and [ 000 1 ¯ 0001 ] directions. A hexagonal pyramid with the apex pointing to [0001] direction is generated as the sublimation‐induced equilibrium crystal structure of wurtzite GaN. The observed phenomena is attributed to the asymmetric surface energies in wurtzite GaN.